Acute renal failure in patients with COVID-19: A literature review - Girão , Milena Maria Felipe; Carvalho, Harnowd Felipe Nogueira de; Morais , Tatiane Ribeiro de; Albuquerque, Lucas Pereira; Silva , Metton Ribeiro Lopes e; Silva, Claudio Gleidiston Lima da; Santos, Maria do Socorro Vieira dos (Seven Editora, 2023)
Introduction: Acute kidney injury (AKI) is a serious complication of the disease caused by the new SARS-CoV-2 and derives from numerous factors such as direct damage to the renal structures by the virus, the use of nephrotoxic drugs and the cytokine storm in response to the etiologic agent. Objective: In view of the relevance of AKI in the clinical outcome, the present study aimed to list the main aspects of the development of this complication in patients with COVID-19. Methods: A literature review was performed using the Virtual Health Library and Pubmed databases, adopting the descriptors “acute kidney injury” and “coronavirus 19”. Results: 635 articles related to the topic were found, of which, after applying the inclusion and exclusion criteria, 23 studies were selected to integrate this review. The articles included were classified as retrospective cohorts and their samples were composed of individuals from Europe, Asia and the Americas. Discussion: Proteinuria, hematuria, leukocyturia and AKI were common clinical findings of renal impairment. AKI is a modifiable and multifactorial risk factor, uncommon in mild and moderate cases and common in severe cases. Age greater than 65 years, presence of comorbidities and laboratory tests with relevant alterations are important risk factors involved in AKI. Patients with stage 3 AKI required renal replacement therapy and were associated with an increased risk of developing chronic kidney disease. Conclusion: In patients with COVID-19 admitted to the ICU, a careful analysis of the clinical history and strict monitoring of laboratory tests are necessary to prevent the development of AKI.DOI:https://doi.org/10.56238/emerrelcovid19-063